Impact of Food Safety Standards on Processed Food Exports from Developing Countries - Juthathip Jongwanich (Asian Development Bank (ADB), 2009)
This paper examines the impact of food safety standards on processed food exports in developing countries. An intercountry cross-sectional econometric analysis of processed food exports in developing countries was undertaken. The Sanitary and Phytosanitary Standard (SPS) is incorporated into the model to capture the impact of food safety standards. The empirical model shows that food safety standards imposed by developed countries tend to have a negative implication for processed food exports from developing countries. Since SPS is less transparent than tariffs or quotas, practically, there is ample room for developed countries to tweak the standards to be stronger than necessary to achieve optimal levels of social protection, and to twist the related testing and certification procedures to make their own competing products competitive with imports. However, because of the potential benefits that could emerge from imposing food safety standards such as a reduction of transaction costs and trade friction, developing countries should view SPS not just as a trade barrier but an opportunity to upgrade quality standard and market sophistication. Multilateral efforts are needed to mobilize additional financial and technical assistance to help redress constraints in developing countries in meeting the required food safety standards imposed by developed countries.
hdl:11540/1807
Keywords: L66; 330; Food Safety Standards; Processed food trade; developing countries; Lebensmittelsicherheit; Lebensmittelsicherheit; International; Agraraußenhandel; Entwicklungsländer; Welt